Characterisation of Non-Saccharomyces Yeasts Using Different Methodologies and Evaluation of their Compatibility with Malolactic Fermentation - du Plessis, H.W.; du Toit, M.; Hoff, J.W.; Hart, R.S.; Ndimba, B.K.; Jolly, N.P. (South African Journal of Enology and Viticulture, 2017)
Although Saccharomyces cerevisiae is the yeast species predominantly used for alcoholic fermentation, non-Saccharomyces yeast species are also important because they produce secondary metabolites that can contribute to the final flavour and taste of wines. In this study, 37 strains representing seven non-Saccharomyces species were characterised and evaluated for potential use in wine production, as well as for their effects on malolactic fermentation (MLF). Contour-clamped homogeneous electric field (CHEF) gel electrophoresis and matrix-assisted laser desorption ionisation using a time-of-flight mass spectrometer (MALDI-TOF MS) were used to verify species identity and to determine intra-species variation. Extracellular enzyme production, malic acid degradation and the fermentation kinetics of the yeasts were also investigated. CHEF karyotyping and MALDI-TOF MS were useful for identifying and typing Hanseniaspora uvarum, Lachancea thermotolerans, Candida zemplinina (synonym: Starmerella bacillaris) and Torulaspora delbrueckii strains. Only H. uvarum and Metschnikowia pulcherrima strains were found to have β-glucosidase activity. M. pulcherrima strains also had protease activity. Most of the strains showed limited malic acid degradation, and only Schizosaccharomyces pombe and the C. zemplinina strains showed mentionable degradation. In synthetic wine fermentations, C. stellata, C. zemplinina, H. uvarum, M. pulcherrima and Sc. pombe strains were shown to be slow to medium fermenters, whereas L. thermotolerans and T. delbrueckii strains were found to be medium to strong fermenters. The effect of the yeasts on MLF varied, but inhibition was strain dependent.